Civic space—and desire—deranged : from Le Corbusier to Georges Perec (2020)
The titular phrase “civic spaces and desire” reminds me of the opening lines of Gilles Deleuze and Félix Guattari’s wonderful book, Kafka: Toward a Minor Literature: “How can we enter into Kafka’s work?” they ask. “This work is a rhizome, a burrow. . . . We will enter, then, by any point whatsoever; none matters more than another, and no entrance is more privileged even if it seems an impasse, a tight passage, a siphon” (Deleuze and Guattari, 1986, p. 3). How, then, can we enter the burrow or rhizome of civic spaces and desire? Besides the city gates, the main thoroughfares and the subterranean watercourses, the obvious points of entry are “civic spaces” on the one hand and “desire” on the other hand, but I hesitate to choose between them since it is not entirely clear which of them should come first, nor whether they are in fact even separable.